Stimulus-secretion coupling in rat mast cells: inactivation of extracellular calcium dependent secretion. - Cochrane, D E (1982)
1. Stimulation by compound 48/80 of mast cells deprived of Ca failed to release histamine. Secretion of histamine was elicited from such cells by the subsequent introduction of Ca. 2. Histamine secretion declined as the interval between stimulation by compound 48/80 and the introduction of Ca increased. This decline is called inactivation. 3. The addition of the ionophore, A23187, with Ca restored maximum histamine secretion overcoming inactivation. 4. Increasing the concentration of Ca introduced after stimulation, from 2 to 8 mM, or to 20 mM reduced the amount of histamine released. This reduction was proportional to the interval between stimulation and the introduction of Ca. The addition of A23187 with the higher concentrations of Ca fully restored histamine secretion. 5. Stimulation of mast cells in Ca-free media by the secretagogues polymyxin B or bradykinin, and the subsequent introduction of Ca, resulted in a similar inactivation or decline in histamine release. 6. Mast cells inactivated by compound 48/80 stimulation in Ca-free media showed no increase in histamine release when the secretagogues polymyxin B plus Ca or bradykinin plus Ca were added. However, when A23187 plus Ca was added, a full secretory response was obtained. 7. It is suggested that the process of inactivation involves time-dependent change in the Ca permeability of the mast cell membrane. The concentration of introduced Ca is suggested to influence the regulation of this permeability.